Sub-chronic exposure to realgar induces liver injury via upregulating the TXNIP/NLRP3 pathway and disturbing bile acid homeostasis in mice. (5th December 2021) - Li, Aihong; Wu, Xinyu; Yang, Jing; Li, Jian; Guo, Haoqi; Zhang, Yuwei; Jiang, Hong; Huo, Taoguang
Abstract: Ethnopharmacological relevance: Realgar is a traditional Chinese medicine used in China for a long history. Long-time or excessive use of realgar causes liver injury. However, its underlying mechanism is not fully clarified. Aim of the study: In this study, we investigated the toxic effect of sub-chronic exposure to realgar on mice liver, and further revealed its underlying mechanism focused on the TXNIP/NLRP3 pathway and bile acid homeostasis. Material and methods: Mice were divided into control and different doses of sub-chronic realgar exposed groups. Total arsenic levels in the blood and liver were determined by atomic fluorescence spectrometry. The effect of realgar on liver function was evaluated by biochemical analysis and histopathological examination. Assay kits were applied for the measurement of oxidative stress indexes, MPO and plasma inflammatory cytokines. The mRNA and proteins involved in the TXNIP/NLRP3 and NF-κB pathways were determined by RT-qPCR, western blot, Immunofluorescence and Immunohistochemistry. UHPLC/MS/MS was used for the quantitative analysis of bile acids (BAs) in mice plasma, liver and urine. The genes related to BAs metabolism were measured by RT-qPCR. Results: Sub-chronic exposure to realgar led to arsenic accumulation and caused oxidative damage and inflammatory infiltration in mouse liver, finally resulting in liver injury. Realgar treatment activated the NF-κB pathway and significantly upregulated the TXNIP/NLRP3 pathway in mouse liver. Realgar altered the metabolic balance of BAs, which is related to the abnormal expression of BAs transporters and enzymes. Conclusion: Sub-chronic exposure to realgar caused liver injury in mouse, and the mechanism may involve the upregulation of the TXNIP/NLRP3 pathway and disordered BAs homeostasis. Graphical abstract: Image 1 Highlights: Sub-chronic realgar exposure caused liver injury in mouse. Realgar induced oxidative damage and inflammation in the mouse liver. Realgar upregulated the TXNIP/NLRP3 pathway in the mouse liver. Realgar disturbed bile acid homeostasis in the mouse liver, plasma and urine.